Antibacterial substances produced by pathogen inhibitory gut bacteria in Labeo rohita: Physico-chemical characterization, purification and identification through MALDI-TOF mass spectrometry. (May 2019) - Mukherjee, Anjan; Banerjee, Goutam; Mukherjee, Piyali; Ray, Arun Kumar; Chandra, Goutam; Ghosh, Koushik
Abstract: Application of antibiotics to combat bacterial diseases in fish has been criticized due to likely emergence of drug resistance. Therefore, investigation of new bioactive compounds from natural sources has been taken into account. This study was designed to purify and characterize the bioactive compound in the cell free supernatant (CFSs) of autochthonous gut bacteria ( Bacillus methylotrophicus KU556164, B. amyloliquefaciens KU556165, Pseudomonas fluorescens KU556166 and B. licheniformis KU556167) isolated from rohu, Labeo rohita . CFSs were antagonistic to fish pathogenic Aeromonas spp., moderately thermo-tolerant and active in wide range of pH (5–11). Antibacterial activity of the CFSs was reduced by the action of proteases (e.g., Proteinase K and Trypsin), indicating proteinaceous nature of the bioactive compound like the bacteriocins. Three-step purification procedure resulted in recovery of 16.97%, 18.04%, 33.33% and 6.38% activity of the antimicrobial protein produced by B. methylotrophicus, B. amyloliquefaciens, P. fluorescens and B. licheniformis, respectively. Purification at each step revealed decrease in protein content with gradual increase in the specific activity of the antimicrobial protein. The purified antibacterial compound ranged between 18.2 and 25.6 kDa. Identification through MALDI-TOF MS/MS and database search through Mascot search engine predicted that the bactericidal compound belonged to either alkaline proteases, or, transcriptional regulator and some hypothetical proteins. Apart from potential technological application of the antibacterial compound, the present study might show promise for application of gut-associated bacteriocinogenic bacteria to control diseases in fish caused by pathogenic bacteria. Highlights: Bacteriocinogenic microorganisms is of interest to replace antibiotics. Gut bacteria from Labeo rohita produced antimicrobial proteins (AMPs). AMPs were antagonistic to Aeromonads. Purified AMPs ranged 18.2–25.6 kDa, stable to pH and temperature variations. The study suggests potential application of the AMPs in fish health management.